Chromosomal instability mediated by non-B DNA: Cruciform conformation and not DNA sequence is responsible for recurrent translocation in humans - Inagaki, Hidehito; Ohye, Tamae; Kogo, Hiroshi; Kato, Takema; Bolor, Hasbaira; Taniguchi, Mariko; Shaikh, Tamim H.; Emanuel, Beverly S.; Kurahashi, Hiroki (Genome Research, 2009)
Chromosomal aberrations have been thought to be random events. However, recent findings introduce a new paradigm in which certain DNA segments have the potential to adopt unusual conformations that lead to genomic instability and nonrandom chromosomal rearrangement. One of the best-studied examples is the palindromic AT-rich repeat (PATRR), which induces recurrent constitutional translocations in humans. Here, we established a plasmid-based model that promotes frequent intermolecular rearrangements between two PATRRs in HEK293 cells. In this model system, the proportion of PATRR plasmid that extrudes a cruciform structure correlates to the levels of rearrangement. Our data suggest that PATRR-mediated translocations are attributable to unusual DNA conformations that confer a common pathway for chromosomal rearrangements in humans.